CHARACTERISTIC FEATURES OF THE SEMANTICS OF COLOR IN THE PHRASEOLOGY OF THE UZBEK LANGUAGE - Djalilova Sarvaroy Mekhrojovna; Khamidova Farangiz Erkinovna (Bright Mind Publishing, 2025)
The article examines the semantics of color in the phraseological units of the Uzbek language, emphasizing the cultural, social and religious aspects of color perception. The study is based on the analysis of phraseological units associated with white, black, green, red and blue colors. The revealed features show that colors in the Uzbek language not only reflect natural phenomena, but also are symbols of social status, emotions and religious values. The results emphasize the importance of color semantics as a key element reflecting the mentality of the Uzbek people and their cultural traditions. The study offers an in-depth look at the interaction of color and language, which may be useful for further linguistic and cultural studies.
Keywords: Phraseology, Semantics of color, Uzbek language, Linguoculturology, Cultural traditions, Emotional symbolism, Social status, Religious symbolism, Natural associations.